The Influence Of Reference Group And Lifestyle On Consumer Attitudes And Decisions To Buy Red Rice In Medan City - Nana Trisna Mei Br Kabeakan; Yudha Andriansyah Putra (JASc (Journal of Agribusiness Sciences), 2019)
Red rice has long been known to be beneficial to health as well as staple food, but red rice is generally less popular as a staple food, red rice is also limited in the market and the price is relatively higher compared to white rice. Consumers' decision to consume red rice does not just happen, given that most Indonesians are used to consuming white rice. There are several factors that influence consumer decisions before making a decision to purchase red rice. This study aims to determine and analyze the influence of reference group  and lifestyle on the attitudes and decisions of consumers to buy red rice in the city of Medan. The number of samples in this study were 100 people using purposive sampling technique. The data were analyzed by using path analysis. The result of the research showed  the reference group did not have a positive and significant effect on the attitudes of consumers to buy red rice in the city of Medan, the reference group did not have a positive and significant effect on consumers 'decision to buy red rice in Medan, the reference group indirectly had no positive influence on consumers' decision to buy red rice in Medan through attitude as an intervening variable, lifestyle had a positive and significant effect on the attitudes of consumers to buy red rice in the city of Medan, lifestyle had a positive and significant effect on consumers 'decision to buy red rice in the city of Medan, lifestyle indirectly had a positive and significant influence on consumers' decision to buy red  rice in the city of Medan through attitude as an intervening variable and attitude had a positive and significant effect on the decision of consumers to buy red rice in the city of Medan